STRATEGIES TO EXPAND THE PRODUCTION OF HIGH VALUE-ADDED PRODUCTS IN THE INDUSTRY (ON THE EXAMPLE OF UZBEKISTAN) - Farmonova Maftuna Norpulat qizi; Usmanova Dilnoza Xodjimuratovna (Web of Journals Publishing, 2025)
This article analyzes the strategies of expanding the production of high value-added products in the industry of Uzbekistan. The technological level, export potential, localization level and international competitiveness factors of industrial sectors are deeply studied. According to the results of the analysis, technological modernization, innovative infrastructure, training of qualified personnel and export diversification play an important role in increasing the share of high value-added products. As a conclusion, strategic recommendations have been developed.
Keywords: Industry, high added value, strategy, innovation, export, Uzbekistan, digitalization, technological modernization.